Utilization of Kartu Amalan Media to Improve Mathematics Learning Outcomes of Grade VI Students on Integer Numbers - Ulfah, Farida; Wulandari, Tri Candra (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2026)
This study aims to improve the learning achievement of sixth-grade students at SD Islam Sabilillah Malang on integer material through the implementation of the Think Pair Share (TPS) learning model assisted by Kartu Amalan media. Kartu Amalan consists of Kartu Kebaikan representing positive integers and Kartu Kekurangan representing negative integers, making the abstract concept of integers more concrete and meaningful for students. This study employed a Classroom Action Research (CAR) design consisting of two cycles. Data were collected through student activity observation sheets and AKM-based written tests. The results showed an increase in the average learning achievement score from 67.32 (pre-cycle) to 79.00 in cycle I and 83.19 in cycle II. The percentage of students who met the minimum learning objective criteria increased from 38.71% to 87.09%. Student activity on Think, Pair, and Share indicators also improved significantly in each cycle. It is concluded that the TPS learning model assisted by Kartu Amalan media is effective in improving students’ mathematics learning achievement on integer numbers.